2010
DOI: 10.1007/s12594-010-0035-7
|View full text |Cite
|
Sign up to set email alerts
|

Textural characteristics, distribution pattern and provenance of heavy minerals in glacial sediments of Schirmacher Oasis, east Antarctica

Abstract: Heavy minerals of twenty sediment samples, belonging to polar ice sheet, lake, mainland area and shelf region of Schirmacher Oasis, east Antarctica, have been studied for their textural characteristics, abundance and provenance determination. The heavy crop is represented by zircon, tourmaline, rutile, garnet, hypersthene, hornblende, chlorite, enstatite, lawsonite, kyanite, sillimanite, zoisite, andalusite, spinel, topaz and opaques. The assemblage, in general, is dominated by hornblende-hypersthene-garnet as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The mineralogical composition of sedimentary parent material for the studied soils resembles that of the source rocks -Precambrian gneiss. This agrees with the results of Srivastava et al (2010) on the heavy mineral assemblages from the Schirmacher Oasis sediments which correspond to the local metamorphic bedrock and demonstrate low maturity. In general, that is typical for the sediments, generated within the glacial geosystems (Nesbitt and Young, 1996), where sediment composition is controlled by physical breakdown and fluvial sorting with minimal contribution of biochemical weathering (Caracciolo et al, 2012).…”
Section: Transformation Of Mineral and Organic Components: Microscopisupporting
confidence: 90%
“…The mineralogical composition of sedimentary parent material for the studied soils resembles that of the source rocks -Precambrian gneiss. This agrees with the results of Srivastava et al (2010) on the heavy mineral assemblages from the Schirmacher Oasis sediments which correspond to the local metamorphic bedrock and demonstrate low maturity. In general, that is typical for the sediments, generated within the glacial geosystems (Nesbitt and Young, 1996), where sediment composition is controlled by physical breakdown and fluvial sorting with minimal contribution of biochemical weathering (Caracciolo et al, 2012).…”
Section: Transformation Of Mineral and Organic Components: Microscopisupporting
confidence: 90%
“…grain sizes and texture). Recently, the use of more sophisticated multivariate statistical methods like factor analysis and discriminant functions have yielded more successful results in identifying the correct depositional process and environments and this is supported by the works of [21][22][23][30][31][32]. This study provides the first relatively detailed grainsize analysis of sandstones from part of the Ecca Group in the study area.…”
Section: Introductionmentioning
confidence: 81%
“…The bivariate plots are based on the assumption that statistical parameters reliably reflect differences in the fluid-flow mechanisms of sediment transportation and deposition [30]. Several researchers like [19,21,[30][31][32]64] have proven and documented that bivariate plots serve as reliable tools for identifying mechanisms of different environments of sedimentation. Furthermore, they reported that the bivariate plots are the most important and frequently used plots [4,63,65,66] These plots have also been attempted to differentiate between marine and fluvial sands.…”
Section: Bivariate Plots Of Statistical Parametersmentioning
confidence: 99%
“…The poor sorting of the sediments from the lakes and the ice-free area is also primarily the result of the activity of wind and meltwater. The source of the sediments consists mainly of the highly metamorphosed host rocks and intrusions, as shown by the heavy minerals: zircon, tourmaline, rutile, garnet, hornblende, zoisite, lawsonite, chlorite, spinel, topaz and opaque minerals (Srivastava et al, 2010). These minerals are set free from the host rock by glacial erosion and frost action.…”
Section: Discussionmentioning
confidence: 99%
“…Modern glacial sediments accumulate due to weathering of the basement, deposition of sediments by the ice sheet, meltwater currents, settling of sediments in lakes, wind activity, etc. The oasis has been studied for its general geology (Sengupta, 1986;Singh, 1986), heavy minerals (Lal, 1986;Srivastava et al, 2010), the geochemistry of the basement (Hoch & To-bschall, 1988;Hoch, 1999;Hoch et al, 2001), structural and thermal characteristics of graphite (Parthasarathy et al, 2003), bedrock topography and subsurface structure (Sundararajan & Rao, 2005), Holocene climate change (Sharma et al, 2007), climatological interpretation of clay minerals (Srivastava et al, 2011), and the geomorphological evolution of the oasis, including modeling of its lacustrine regime from 13 ka ago to nowadays (Phartiyal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%